In vitro photoprotective attributes from the Chlorella vulgaris cultivated in photobioreactor - Santos, Bruna Bertoloni dos (2022)
Chlorella vulgaris, a species of green microalgae, is an eukaryotic microorganism with high photosynthetic ability. C. vulgaris is found in different environments, predominantly in fresh and salt water, where there is exposure to high levels of UV radiation and extreme survival conditions. In response to these challenges, C. vulgaris produces several secondary metabolites that may have antioxidant properties. Considering the field of Cosmetology, through studies carried out so far, C. vulgaris showed potential to develop attributes, like preventing skin blemishes, repairing skin damage and collagen, inflammation inhibition, hydration and protection against damage caused by solar radiation, among other features. Due to these, the genus Chlorella has been gaining visibility scientific and commercially. The use of microalgae biomass uses to be seen as ecologically correct mainly due to the possibility of using it in various fields of application, such as in foods, source of biodiesel, pharmaceuticals and cosmetics. Besides, there are the possibility of directing the production of substances of interest through different cultivation strategies. Thus, microalgae extract can be a relevant type of constituent in products considered natural for sun protection. Based on this, this project evaluated employability of C. vulgaris as a photoprotective and photostabilizing ingredient. Thus, different conditions of cultivation were evaluated with different concentrations of nitrogen, obtaining better results in the 3N (8.82 mM) condition. After obtaining, preparing and characterizing the C. vulgaris extract, photoprotective formulations were prepared with 1.0, 5.0% and 10.0% extract. The photoprotective efficacy of the formulation was verified through a significant increase in SPF when using the C. vulgaris extract it at 10.0%, however, the extract did not show a photostabilizing efficacy in the formulation at any of the concentrations tested.